2015
DOI: 10.5713/ajas.15.0034
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Relationship of Productive Life, Production and Type Traits of Korean Holsteins at Early Lactations

Abstract: The present study was performed to study the genetic relationship of productive life with production and type traits of Korean Holsteins at first three lactations. The data for the analysis from 56,054, 28,997, and 11,816 animals of first, second and third parity cows which were born from 2006 to 2011 were collected by Dairy Cattle Improvement Center, National Agricultural Co-operative Federation. Milk, protein and fat yields adjusted for 305 days and average somatic cell score considered as production traits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 14 publications
4
10
1
2
Order By: Relevance
“…Similar results can be seen in Harris et al (1992) and Vukašinović et al (1995). However, Wasana et al (2015) reported lower estimates of genetic correlation of productive life and production traits in three parities for Korean Holstein. Their estimates were in the range of 0.04-0.35 for milk yield and 0.02-0.18 for fat yield.…”
Section: Resultssupporting
confidence: 74%
“…Similar results can be seen in Harris et al (1992) and Vukašinović et al (1995). However, Wasana et al (2015) reported lower estimates of genetic correlation of productive life and production traits in three parities for Korean Holstein. Their estimates were in the range of 0.04-0.35 for milk yield and 0.02-0.18 for fat yield.…”
Section: Resultssupporting
confidence: 74%
“…A favorable positive correlation was observed between the production trait FM305 and functional trait LPL ( r , LPL, FM305 g = 0.43) mainly because the dairy cattle producers prefer to keep high-milk-yielding cattle in the herd. The positive genetic correlation between FM305 and LPL was also reported by Irano et al (2014) and Wasana et al (2015). Our results also demonstrate an unfavorable positive correlation between FM305 and DO ( r , DO, FM305 g = 0.14), indicating that the genetic selection for high milk yield could reduce the fertility of dairy cattle as previously pointed out by Van Raden et al (2004).…”
Section: Estimation Of Genetic Parameterssupporting
confidence: 88%
“…However, the milk heritability was slightly lower than the values reported by Irano et al (2014), Tsuruta et al (2005), Pritchard et al (2013), which were 0.28, 0.4, and 0.3, respectively. The heritability of LPL was also slightly lower than the value (0.13) reported by Wasana et al (2015).…”
Section: Estimation Of Genetic Parameterscontrasting
confidence: 71%
“…However, the genetic correlations between SCS and TBCS with PY and FY were of opposite signs, being negative for fat and positive for protein. Wasana et al (2015) reported negative genetic correlations between SCS and the PY (−0.04) and FY (−0.02), but with values close to zero; while Pritchard et al (2013) found positive genetic correlations between SCS and the PY (0.13) and FY (0.07). The reduced value of most of these correlations indicates only little association between the genes that increase these milk solids and genes that increase susceptibility to mastitis.…”
Section: Discussionmentioning
confidence: 95%